An Investigation of scaffolding strategies to support structured inquiry language teaching to novice learners in a Primary school setting - Amelie Langdon; Jillian Pandor (Universitat Jaume I. Department of English Studies, 2020)
It is believed that Inquiry-Based Learning (IBL) affords relevant and meaningful L2 instruction given its contextualised and experiential approach. IBL, which only recently gained popularity in the L2 classroom, strongly differs from that of traditionally didactic methodologies and can present challenges for L2 educators. Research shows that many struggle to adopt a well-rounded inquiry approach and instead tend to over-rely on strategies aiming to make meaning comprehensible to learners, thus neglecting a focus on language form, language use and inquiry skills. This literature review examines current trends in L2 teaching and learning when implementing a structured inquiry approach in the primary school setting and attempts to uncover and evaluate various scaffolding strategies that can be employed to support a more holistic approach to IBL. The language scaffolding practices described in this paper are categorised into four areas of focus: focus on meaning, focus on form, focus on language use, and inquiry skills.